2022
DOI: 10.3390/microorganisms10020454
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Adhesion: From Hydrophobic to Receptor-Ligand Interactions

Abstract: Adhesion is crucial for the infective lifestyles of bacterial pathogens. Adhesion to non-living surfaces, other microbial cells, and components of the biofilm extracellular matrix are crucial for biofilm formation and integrity, plus adherence to host factors constitutes a first step leading to an infection. Adhesion is, therefore, at the core of pathogens’ ability to contaminate, transmit, establish residency within a host, and cause an infection. Several mycobacterial species cause diseases in humans and ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 206 publications
(254 reference statements)
0
3
0
Order By: Relevance
“…Infection begins with adhesion to host tissues and cells. The hydrophobicity of the cell wall is a factor that affects the ability to adhere [ 46 ]. The results of this study showed that the number of bacteria capable of adhesion and invasion was higher in the M .…”
Section: Discussionmentioning
confidence: 99%
“…Infection begins with adhesion to host tissues and cells. The hydrophobicity of the cell wall is a factor that affects the ability to adhere [ 46 ]. The results of this study showed that the number of bacteria capable of adhesion and invasion was higher in the M .…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify whether the HA derivatives have antimycobacterial activities, we assessed these activities in planktonic and stress conditions with high glycerol concentrations leading to biofilm development. Biofilm conditions are indeed known to better mimic stressful in vivo conditions [26][27][28]. These antimycobacterial activities were assessed using three strains, harboring various characteristics, among others, the presence or absence of PDIM lipids in their cell wall: the H37Ra M. tuberculosis strain is PDIM-negative and is a slow-growing strain; the M. marinum is PDIM-positive and a slow-growing mycobacterium (however, in planktonic cultures, it grows faster than M. bovis BCG or H37Ra M. tuberculo-sis strains); and the M. bovis BCG is PDIM-positive and a slow-growing mycobacterium.…”
Section: Ha Compounds Present Antimycobacterial Activitiesmentioning
confidence: 99%
“…Diverse factors drive mycobacterial biofilm formation, as has been reviewed elsewhere [22][23][24] and in detail for multiple mycobacterial species by Chakraborty and Kumar [25]. For the two most highly studied species, M. tuberculosis and M. smegmatis, the most consistent association has been with lipids, including free mycolic acids (FMA) [11,13], mycolyl diacylglycerides (MDAG) [26], monomeromycolyl diacylglycerides (MMDAG) [7,27], mycolate wax esters (MWE) [7,8,27] and, in M. smegmatis, glycopeptidolipids (GPL) [9,28].…”
Section: Introductionmentioning
confidence: 99%